5271 sayılı ceza muhakemesi kanunu’na göre tutuklama ve haksız tutuklama tazminatı - Çetin, Seydi (My University, 2024)
Hukuk devletinin bir gereği olarak, koruma tedbirlerinin hukuka aykırı şekilde uygulanması sebebiyle hak ve hürriyetleri ihlal edilen kişilerin bu zararlarının tazmini gerekmektedir. Bu çerçevede, bu tezin konusu, ceza muhakemesinde haksız tutuklama sebebiyle tazminat davasıdır. Bu çalışmada, tutuklamanın koşulları ve tutuklamanın hukuki niteliği, tutuklama tedbirini verecek merci, hakim önüne çıkarılma, tutuklama kararlarına karşı kanun yolları ve özel tutuklama halleri ele alınacaktır. Bununla birlikte, tutuklamanın hukuka aykırı olması halinde ödenmesi gereken tazminat türleri olan maddi ve manevi tazminat kavramları ile CMK m.141’de yer alan tazminat nedenleri incelenmiştir. Son olarak, tazminat başvurusu yapabilecekler, tazminat başvurusu yöntemi, görevli mahkeme, tazminatın hesaplanması, tazminat kararına karşı kanun yolu, rücu ve tazminatın geri alınması halleri ve kavramları irdelenmiştir.

As a requirement of the rule of law, the damages of those whose rights and freedoms have been violated due to the unlawful application of protection measures must be compensated. In this context, the subject of this thesis is the lawsuit for compensation due to unfair detention in criminal procedure law. In this study, the conditions of arrest and the legal nature of arrest, the authority that will issue the arrest warrant, being brought before a judge, legal remedies against arrest decisions and special cases of arrest will be discussed. In addition, the concepts of material and moral compensation, which are the types of compensation that must be paid in case the arrest is unlawful, and the reasons for compensation in CMK article 141 have been examined. Finally, those who can apply for compensation, the method of applying for compensation, the competent court, the calculation of compensation, the legal remedy against the compensation decision, the cases and concepts of recourse and withdrawal of compensation are examined.
Keywords: arbitrary detention; Arrest; calculation of damages; case of damage; Compensation (Law); detention; Devletin sorumluluğu; False imprisonment; Government liability; haksız tutuklama; Koruma tedbirleri; reason of damage; tazminat davası; Tazminat hukuku; tazminat nedenleri Protection measures; tazminatın hesaplanması; Tutuklama; Türkiye; Yanlış tutuklama